Navigating Regime Complexes in Turbulent Times—The EU's Interaction with Other International Organizations in Crises - Benjamin Daßler; Sandra Bandemer; Berthold Rittberger; Moritz Weiß (Politische Vierteljahresschrift, 2024)
Over the past decades, the European Union (EU) has confronted multiple crises, which have prompted swift political responses from the EU's member states and institutions. While there is a broad literature about the EU's internal responses to crises, we know much less about the EU's interactions with external actors. Because the EU is part of issue-specific regime complexes, it has cultivated relationships with international organizations (IOs) across a multitude of issues. We argue that during crises, the EU has heightened incentives to complement its internal crisis response by interactions with other IOs that vary in their qualities. How can the EU's external engagement during crises be conceptualized and theoretically explained? Drawing on the regime complexity literature, we identify three different types of interactions among IOs to conceptualize the EU's varying external engagements during crises periods: pooling, division of labor , and competition . We further argue that under the condition of regime complexity, the choice of interorganizational interaction is shaped by the convergence of means and ends among the respective dyads of IOs. To illustrate the usefulness of our typology for the study of the EU's external responses to crises, as well as the plausibility of our argument, we analyze three instances of EU–IO relationships in crisis contexts: pooling between the EU and the International Monetary Fund (IMF) to address the sovereign debt crisis, division of labor between the EU and the North Atlantic Treaty Organization (NATO) in response to Russia's war of aggression against Ukraine, and competition between the EU and the European Court of Human Rights (ECtHR) during the "migration crisis." – – In den letzten Jahrzehnten sah sich die Europäische Union (EU) mit einer Reihe von fundamentalen Krisen konfrontiert, die rasche politische Reaktionen ihrer Mitgliedstaaten und Institutionen erforderten. Während die Literatur, die sich mit den internen Krisenpolitiken der EU beschäftigt inzwischen sehr umfangreich ist, wissen wir viel weniger über die Interaktionen der EU mit externen Akteuren. Da die EU Teil von politikfeldspezifischen Regimekomplexen ist, hat sie über die Zeit diverse Beziehungen zu internationalen Organisationen (IOs) in einer Vielzahl von Bereichen aufgebaut. Wir argumentieren, dass die EU in Krisenzeiten verstärkte Anreize hat, ihre interne Krisenreaktion durch solche externen Interaktionen mit anderen IOs unterschiedlicher Qualitäten zu ergänzen. Wie können diese externen Interaktionen der EU während Krisen konzeptualisiert und theoretisch erklärt werden? Basierend auf der Literatur zur Regimekomplexität identifizieren wir drei verschiedene Arten von Interaktionen zwischen IOs, um die unterschiedlichen externen Interaktionsformen der EU während Krisenzeiten zu konzeptualisieren: " pooling " , " divison of labour " und " competition " . Wir argumentieren weiter, dass unter der Bedingung von Regimekomplexität die Wahl der interorganisationalen Interaktion durch die Konvergenz von Mitteln und Zielen zwischen den jeweiligen IO-Dyaden geprägt wird. Um die Nützlichkeit unserer Typologie für die Untersuchung der externen Krisenreaktionen der EU und die Plausibilität unseres Arguments zu veranschaulichen, analysieren wir drei Fälle von EU-IO-Beziehungen in Krisenkontexten: Pooling zwischen der EU und dem Internationalen Währungsfonds (IWF) zur Bewältigung der Staatsschuldenkrise; Arbeitsteilung zwischen der EU und der North Atlantic Treaty Organization (NATO als Reaktion auf Russlands Angriffskrieg gegen die Ukraine; und Wettbewerb zwischen der EU und dem Europäischen Gerichtshof für Menschenrechte (EGMR) während der sogenannten "Migrationskrise".
Keywords: 320; Crisis politics; European Union (EU); Regime complexity; International organizations; Crisis management; Krisenpolitik; Europäische Union (EU); Regimekomplexität; Internationale Organisationen; Krisenmanagement